Free Translation Strategy in Ya Binti: An Analytical Study on the Delivery of Arab Social Advice into Indonesian - Rahmah, Miftahul; Rahmadon; Oktarina, Mikyal (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study explores the application of free translation techniques in rendering Ya Binti, a culturally rich and rhetorically nuanced Arabic text authored by Sheikh Ali al-Tantawi, into Indonesian. Emphasizing meaning over literal form, the translator employs a variety of strategies such as adaptation, modulation, amplification, and reduction to preserve the text's moral and emotional resonance while ensuring its accessibility to modern Indonesian readers. Drawing from the frameworks of Newmark, Nida and Taber, as well as Molina and Albir, this analysis highlights how linguistic creativity and cultural sensitivity work hand-in-hand in the translation process. The results show that free translation, when applied responsibly, not only conveys the original message but also repositions it within a relevant cultural and communicative context. This approach proves particularly effective for literary and religious texts where literal translation may hinder comprehension or distort meaning. The study concludes that free translation serves as a bridge not a barrier between source and target cultures, enabling deeper understanding and wider appreciation of classical Arabic literature in the Indonesian context.